Subacute massive pulmonary embolism treated with plasminogen and streptokinase. - Ellis, D A (1983)
Major pulmonary embolism occurring insidiously over several weeks (subacute massive pulmonary embolism) has a high mortality and may not respond well to standard anticoagulant or thrombolytic treatment. A priming dose of plasminogen was used to enhance thrombolysis produced by a streptokinase infusion in five consecutive patients with subacute massive pulmonary embolism. In each patient a dramatic clinical improvement occurred with a substantial increase in pulmonary blood flow. All five patients survived to leave hospital. Malignant disease was the underlying cause of embolism in three patients, two of whom died of their malignant disease in the six months after treatment of their pulmonary embolism. The third patient with malignant disease had a choriocarcinoma; at least some of the pulmonary obstruction may have been tumour tissue but this obstruction was dramatically cleared by the treatment. The use of a combination of plasminogen with streptokinase should be considered in severely ill patients with subacute massive pulmonary embolism, particularly if other treatment, including streptokinase alone, has failed.